A Sing & Remember Book - Elkins, Stephen (USA, 1986)
Your child will come to know God in a more personal and powerful way with this Sing and Remember book. Knowing God includes 23 Bible Stories and 23 Scriptures songs. Each reveal an important aspect of Gods character...
Keywords: Bible Stories; Christianity; Juvenile Non-Fiction; Religion